Analysis the Effectiveness of safety and Agricultural Professional Healthy Courses which carried out for farmers - S Moradhaseli; A Mirakzadeh; F Rostami (طب کار)
Introduction: Empowerment and training are so delicate and important factors via that human capital changes in to sustainable capital. Retention and development of labor needs to learning and use the safety and agricultural professional healthy receptions in risky agricultural situation. The main purpose of this study was to analysis the effectiveness of safety and agricultural professional healthy courses which carried out for farmers. Methods: First step of this study was survey about farms educational needs by descriptive - survey method in non experimental research. Effective assessment step done by experimental method with control and experimental groups. Statistical population consisted of 213 farm families from Mahidasht who 140 families selected as sample base on Morgan Sampling table and after need assessment 61 farmers participated in second step of research (experimental plan). Research instrument was questioner that its' Reliability confirmed by Choronbach Alpha coefficient calculation (it was 0.77) and questionnaire's validity confirmed by experts (content validity). Data were analyzed by t and F tests in SPSS 11.5 software. Results: Results showed that the mean of the pretest and posttest of experimental group relatively was 6/62 and 18/88. Also Results of t tests showed there was significant difference between pre-test and post - test in examination group which shows the relative effectiveness of the educational course. Conclusion: According to the results, there was significant difference between score of farmer's knowledge before and after of educational course. Therefore it is necessary to maintain the desired level of farmer's knowledge to pay more attention to the education and with training courses awareness of farmers can be promote.